Perubahan Sosial dan Hukum Perbankan di Indonesia - Novira, Elyana; Pratimaratri, Uning (LPPM Universitas Ekasakti Padang, 2024)
Change requires law if it is to be carried out in an orderly and orderly manner. Society's life goes through change and is a natural phenomenon in social phenomena. In the banking world, social change occurs in an evolutionary way. Change has occurred from the time after independence to the present. Various economic policies set by the government, such as economic policies in the 1980s, economic liberalization and economic crises in other countries also have an impact on the Indonesian banking world. Especially when the country is experiencing a monetary crisis, banking changes occur significantly, which are regulated in various laws and regulations. Economic globalization and information technology developments bring about social changes in society, including in the banking world, such as changes in society when making banking transactions.